2016
DOI: 10.1080/1744666x.2017.1248410
|View full text |Cite
|
Sign up to set email alerts
|

The long and winding road to IgA deficiency: causes and consequences

Abstract: The most common humoral immunodeficiency is IgA deficiency. One of the first papers addressing the cellular and molecular mechanisms underlying IgA deficiency indicated that immature IgA-positive B-lymphocytes are present in these patients. This suggests that the genetic background for IgA is still intact and that class switching can take place. At this moment, it cannot be ruled out that genetic as well as environmental factors are involved. Areas covered: A clinical presentation, the biological functions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 135 publications
2
23
0
Order By: Relevance
“…There are a few potential explanations for the fact that the SIgA concentration pattern of our BC survivor group did not differ from that of women with no history of cancer. First, low levels of SIgA are typically associated with the occurrence of different clinical diseases and infections [ 77 79 ]. Despite being survivors of BC, women in our study were perfectly healthy; they did not suffer from any post-cancer medical conditions (at least at the time of the saliva collection).…”
Section: Discussionmentioning
confidence: 99%
“…There are a few potential explanations for the fact that the SIgA concentration pattern of our BC survivor group did not differ from that of women with no history of cancer. First, low levels of SIgA are typically associated with the occurrence of different clinical diseases and infections [ 77 79 ]. Despite being survivors of BC, women in our study were perfectly healthy; they did not suffer from any post-cancer medical conditions (at least at the time of the saliva collection).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in humans there are no reported cases of low or no FcαRI expression on myeloid cells, unlike defects reported in FcγRI which correlate with susceptibility to autoimmunity, chronic inflammation and infection, highlighting the potential importance of FcαRI in homeostasis and inflammation in humans. However, it is important to note that IgA deficiencies have been reported in humans, which have been associated with increased susceptibility to infectious diseases and autoimmunity …”
Section: Serum Iga and Fcαrimentioning
confidence: 99%
“…[1] However, other studies have noted the existence of immature IgA positive B cells in SIgAD patients, suggesting that in some cases the defect is in maturation, rather than class switching of B cells. [58] T and B cells have a higher rate of spontaneous and induced apoptosis in patients with CVID, and Yazdani and colleagues have recently suggested that the same mechanism may be present in those with SIgAD, although this mechanism has yet to be confirmed in individuals with SIgAD. [59] Additionally, SIgAD has been transferred between patients via bone marrow grafting, which further suggests a defect in immune cells.…”
Section: Mechanisms Of Autoimmunity In Iga Deficiencymentioning
confidence: 99%
“…[61] Mutations in the TACI gene have also been implicated in certain cases of SIgAD. [58] While this mechanism may be at play for certain associations, no single mutation has yet been found to explain the correlation of SIgAD with any specific autoimmune disease, or autoimmunity in general. If a single gene mutation associated with SIgAD predisposes to autoimmunity, it appears that additional mechanisms must also be at play for any individual to develop autoimmune manifestations.…”
Section: Mechanisms Of Autoimmunity In Iga Deficiencymentioning
confidence: 99%